1987
DOI: 10.1038/328251a0
|View full text |Cite
|
Sign up to set email alerts
|

Degree of methylation of transgenes is dependent on gamete of origin

Abstract: Data derived from both pronuclear transplantation experiments and classical genetic experiments indicate that the maternal and paternal genetic contributions to the mammalian zygote nucleus do not function equivalently during subsequent development. These observations have been interpreted as resulting from differential 'genome imprinting' during male and female gametogenesis. The molecular mechanism responsible for genome imprinting is unknown, but data gathered to date require that the mechanism fulfill at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
145
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(152 citation statements)
references
References 1 publication
4
145
0
3
Order By: Relevance
“…The silent maternally inherited copies were highly methylated. Since then, additional examples have been reported, all but one of which is maternally methylated (Hadchouel et al 1987;Reik et al 1987;Sapienza et al 1987;Sasaki et al 1991;Ueda et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silent maternally inherited copies were highly methylated. Since then, additional examples have been reported, all but one of which is maternally methylated (Hadchouel et al 1987;Reik et al 1987;Sapienza et al 1987;Sasaki et al 1991;Ueda et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This covalent modification of DNA has been implicated in the perpetuation of the imprinting state in X chromosome inactivation, on the basis of the observation that genes on the inactive X chromosome are more highly methylated than their counterparts on the active X (for review, see Riggs and Pfeifer 1992). In addition a set of transgenes in mice exhibit parent-of-origin differences in DNA methylation, and in at least one instance, the methylation acts to silence the expression of the transgene (Hadchouel et al 1987;Reik et al 1987;Sapienza et al 1987;Swain et al 1987;Chafflet et al 1991;Sasaki et al 1991;Ueda et al 1992). In all but one of these transgenic mouse lines, the transgene becomes methylated after passage through the female germline.…”
mentioning
confidence: 99%
“…However, the environment can stably influence epigenetic marks, which suggest that transgenerational epigenetic inheritance exists. The first evidence that epigenetic marks could indeed be inherited across more than one generation involved transgenes (Allen et al, 1990, Sapienza et al, 1987, Swain et al, 1987. More recently, Lang-Mladek et al, showed in plants that, after extreme temperature or UV-B stress, a silent transgene and several transposable elements were activated, and these changes were heritable for two generations (Lang-Mladek et al, 2010).…”
Section: Epigenetic Memory and Inheritancementioning
confidence: 99%
“…] Genomic imprinting is an epigenetic modification of the gamete or zygote that leads to preferential expression of a specific parental allele in somatic cells of the offspring. The mechanism of imprinting is unknown but it is thought to involve CpG island methylation (Sapienza et al 1987;Sutcliffe et al 1994), antisense transcripts (Wutz et al 1997), short repeat elements (Szebenyi and Rotwein 1994), and/or trans-acting binding proteins that may interact with one or more of these sequences (Bell and Felsenfeld 2000;Hark et al 2000;Srivastava et al 2000). One of the most surprising recent discoveries in the study of genomic imprinting is that imprinted genes are grouped in large multigene domains Ainscough et al 1998;Feinberg 1999).…”
mentioning
confidence: 99%